Primary Pulmonary Carcinomas with Spindle and/or Giant Cell Features: A Review with Emphasis in Classification and Pitfalls in Diagnosis - Cesar A. Moran (Diagnostics, 2023)
Primary carcinomas of the lung are vastly represented by the conventional types of adenocarcinomas or squamous cell carcinomas. However, there are other types of non-small cell carcinomas that although uncommon represent a meaningful group that often pose a problem not only in diagnosis but also in classification. Spindle cell and/or giant cell carcinomas, although uncommon represent an important group of primary lung carcinomas. Important to highlight is that current criteria are rather ambiguous and likely not up to date, which renders the classification of these tumors somewhat more obscure. In addition, with the daily use of immunohistochemical stains, the classification of these tumors may also pose a different problem in the proper allocation of these tumors. Proper classification is highly important in the selection process that takes place using such material for molecular analysis. The current molecular characteristics of these tumors are limited and lack more in-depth studies and analyses that can provide specific targets for the treatment of patients with these tumors. The current review attempts to highlight the shortcomings in the current classification and definitions of these neoplasms as well as the more current view regarding these tumors when the use of immunohistochemical stains is employed.